A Custom Microcontrolled and Wireless-Operated Chamber for Auditory Fear Conditioning - Amaral-Júnior, Paulo Aparecido; Mourão, Flávio Afonso Gonçalves; Amancio, Mariana Chamon Ladeira; Pinto, Hyorrana Priscila Pereira; Carvalho, Vinícius Rezende; Guarnieri, Leonardo de Oliveira; Magalhães, Hermes Aguiar; Moraes, Márcio Flávio Dutra (Frontiers in Neuroscience, 2019)
Animal behavioral paradigms, such as classical conditioning and operant conditioning, are an important tool to study the neural basis of cognition and behavior. These paradigms involve manipulating sensory stimuli in a way that learning processes are induced under controlled experimental conditions. However, the majority of the commercially available equipment did not offer flexibility to manipulate stimuli. Therefore, the development of most versatile devices would allow the study of more complex cognitive functions. The purpose of this work is to present a low-cost, customized and wireless-operated chamber for animal behavior conditioning, based on the joint operation of two microcontroller modules: Arduino Due and ESP8266-12E. Our results showed that the auditory stimulation system allows setting the carrier frequency in the range of 1 Hz up to more than 100 kHz and the sound stimulus can be modulated in amplitude, also over a wide range of frequencies. Likewise, foot-shock could be precisely manipulated regarding its amplitude (from 200 μA to 1500 μA) and frequency (up to 20 pulses per second). Finally, adult rats exposed to a protocol of cued fear conditioning in our device showed consistent behavioral response and electrophysiological evoked responses in the midbrain auditory pathway. Furthermore, the device developed in the current study represents an open source alternative to develop customized protocols to study fear memory under conditions of varied sensory stimuli.